Analisa Pengaruh Kepuasan Pelanggan Dan Excellent Service Terhadap Loyalitas Pelanggan Jasa Rumah Potong Hewan Di UPT. RPH Kota Blitar - Masitah, Dewi; Daroini, Ahsin (Universitas Islam Kadiri, 2024)
Blitar City RPH is a community service facility unit in the provision of safe, healthy, whole and halal meat. The main function of the abattoir is to guarantee the production of good quality meat and provide a sense of physical and spiritual security to consumers, for that UPT. RPH Blitar City continues to strive to meet customer satisfaction by implementing an excellent service system (Excellent Service) to achieve customer loyalty. The purposes of this study are a) To determine the effect of customer satisfaction strategy on Customer Loyalty of Slaughterhouse Services at UPT.RPH Blitar City, b) To determine the effect of Excellence Service on Customer Loyalty of Slaughterhouse Services at UPT.RPH Blitar City and c) To determine the simultaneous effect of customer satisfaction strategies and Excellence Service on Customer Loyalty of Slaughterhouse Services at UPT.RPH Blitar City. The research method used is to use multiple linear regression analysis to determine the significant positive direct effect both partially and simultaneously from the variables studied. The results obtained after carrying out the research are: 1.) Customer satisfaction has a positive and significant direct effect on customer loyalty at UPT. Blitar City RPH. This means that an increase in customer satisfaction will have an effect on increasing customer loyalty at UPT. RPH. Blitar City. 2) Excellent Service has a positive and significant direct effect on customer loyalty at UPT. Blitar City RPH. This means that an increase in Excellent Service will have an impact on increasing Customer Loyalty at UPT. RPH. Blitar City. 3) Customer Satisfaction and Service Excellence have a positive and significant direct effect on customer loyalty at UPT. Blitar City RPH. This means that an increase in Customer Satisfaction and Excellent Service will have an impact on increasing Customer Loyalty at UPT. RPH. Blitar City.